Efektivitas Kitosan Cangkang Kepiting (Scylla serrata) sebagai Koagulan untuk Mengurangi Mikroplastik Polistirena (PS) dalam Air Limbah - Jheni Sriayu Latifa; Indang Dewata (Lembaga Yasin AlSys, 2025)
Microplastic pollution in wastewater has become an urgent environmental issue due to its resistance to degradation and its potential to contaminate the food chain. This study aims to develop a natural coagulant based on chitosan extracted from the waste shells of Scylla serrata (blue swimming crab) as an eco-friendly solution for precipitating polystyrene (PS) microplastics in wastewater. Chitosan was obtained through demineralization, deproteinization, and deacetylation processes, and its effectiveness was tested in a solution containing 50 mg of pure PS microplastics in 250 ml of wastewater. The results showed that the optimum pH for coagulation was 5, achieving a removal efficiency of 98.4%. The optimal chitosan concentration was 0.5%, resulting in a 97.6% removal rate, while the optimal stirring speed of 700 rpm yielded an efficiency of 89.2%. These findings indicate that chitosan derived from crab shell waste is an effective and sustainable coagulant for mitigating microplastic pollution and holds promising potential for application in environmentally friendly wastewater treatment.